Chapter Curriculum globALE: A Global Tool for Professionalising Adult Educators - Lichtenberg, Thomas (Studies on Adult Learning and Education, 2020)
Curriculum globALE (CG) is a cross-cultural core curriculum for training adult educators worldwide. It was developed jointly by the German Institute for Adult Education (DIE) and DVV International. In five modules, it describes the relevant skills needed to lead successful courses and provides guidance on their practical implementation. Curriculum globALE has been applied in many partner countries and in Germany itself. Evaluation results show that CG is a professionalisation tool for adult educators that can be applied successfully world-wide. Graduates confirm a wide use of the newly acquired competences for their educational work. However, the practical application of CG is also faced with a number of challenges.